Challenges in the treatment and prevention of delayed hemolytic transfusion reactions with hyperhemolysis in sickle cell disease patients. Issue 5 (8th March 2019) - Dean, Christina L.; Maier, Cheryl L.; Chonat, Satheesh; Chang, Andres; Carden, Marcus A.; El Rassi, Fuad; McLemore, Morgan L.; Stowell, Sean R.; Fasano, Ross M.
Abstract : BACKGROUND: Delayed hemolytic transfusion reactions (DHTRs) are serious complications of RBC transfusion that can occur in previously alloimmunized patients. Patients who require episodic transfusions during heightened inflammatory states, such as patients with sickle cell disease (SCD), are particularly prone to alloimmunization and developing DHTRs with hyperhemolysis. While efforts to mitigate these hemolytic episodes via immunosuppressive drugs can be employed, the relative efficacy of various treatment options remains incompletely understood. CASE REPORTS: In this study, we explored five patients with SCD and multiple RBC alloantibodies who received various forms of immunosuppressive therapy in an attempt to prevent or treat severe DHTRs. RESULTS: The clinical course for these five patients provides insight into the difficulty of effectively treating and preventing DHTRs in patients with SCD with currently available immunosuppressive therapies. CONCLUSION: Based on our experience, and the current literature, it is difficult to predict the potential impact of various immunosuppressive therapies when seeking to prevent or treat DHTRs. Future mechanistic studies are needed to identify the optimal treatment options for DHTRs in the presence or absence of distinct alloantibodies in patients with SCD.